Optimization of inoculum size & agitation rate on expression of recombinant chitinase in Escherichia coli - Nor Fadzillah Hanis, Abu Sulaiman (2009)
Chitinase generally referred as endochitinases is randomly hydrolyzing chitin to produce N-acetyl-glucosamine. In addition, chitinase play an important role in chitin metabolism of microorganism for production of carbon and energy source. Chitinase can be found in bacteria, fungi, virus and higher plant. There are a lot of applications of chitinase either in pharmaceutical, biopestisides or food industry. For this research, chitinase was expressed in recombinant bacteria using Escherichia Coli as a host. The optimization was carried out by using response surface methodology. Focusing on two parameters which are inoculum size and agitation rate, the optimum condition was identified to enhance the process of chitinase production. The chitinase was expressed in different inoculum size at 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 mL. Then the experiment continued observed in different agitation rate at 50, 100, 150, 200, 250 and 300 rpm. After overall observation, the best range of inoculum size gave between 0.8 mL to 1.2 mL and the range of agitation rate was identified between 230 rpm to 270 rpm. The best range of culture conditions was used for further study using Respond Surface Methodology (RSM). The optimal set of culture conditions for high soluble recombinant chitinase was determined as an inoculum size of 0.98 mL and 244.7 rpm of agitation rate. From the experimental value, the optimal production of recombinant chitinase was achieved 0.376 U/mL. This shows the 1.57-fold increment compared to the initial experiment which produced 0.239 U/mL of chitinase activity. These conditions successfully enhance the production of chitinase by using recombinant protein in Escherichia coli.